(untitled) (Nigerian Journal of Cooperative Economics and Management, 2026)
This study examined the determinants of agricultural credits access among members of farmers’ multipurpose cooperative societies in Anambra state. The Specific Objectives of the study is to analyzed the size of farm land of cooperative farmers and its effect on accessing agricultural credit in Anambra state and to ascertain the effect of years of membership in cooperative organization in accessing agricultural credit in Anambra state. In line with the above objectives, two hypotheses were formulated. This study was particularly anchored on the social exchange theory. It was carried out in three agricultural zones in Anambra state, Nigeria. A multi stage random sampling technique was used to arrive at a sample size of twenty four cooperative societies with membership strength of 286 farmers as sample size. The instrument for data collection was a set of structured questionnaires on a 5-point likert-scale Data was analyzed using the multiple regression models. Model results indicated, Farm size significantly (3.00), t(285) = 13.01, 4.88and 12.91; and p-values = 0.000, respectively have effect on agricultural credit access and years of membership in cooperative significantly (3.85), t(285) = 13.36 and12.86; p-values = 0.000have effect on agricultural credit access. In line with the findings of this study, it is recommended that there should be a deliberate policy that guarantees. Good Policies on land redistribution to make more land available to cooperative farmers, especially the experienced farmers and relevant government agencies should mobilize the rural farmers and encourage them to join cooperative associations, so that they can derive maximum benefit of collective investment of group savings, as well as increase their chances of accessing formal agricultural credit facilities because of the comparative advantages associated with cooperative societies.